The convergence or divergence of labour resources in Poland? - Krupowicz, Joanna (Konwergencja czy dywergencja zasobów pracy w Polsce?, 2020)
Eurostat’s projections indicate that by 2050 Poland will see a significant reduction in and ageing of its labour resources. The country is experiencing a strong polarization of demographic phenomena and disproportions in population structure. The goal of the study was to determine whether Poland’s labour resources are undergoing convergence or divergence. The occurrence of beta, sigma and gamma-convergence in the country’s individual provinces (voivodeships) in the period 2012-2018 was verified. Three models were created (working age population ratio, young-age dependency ratio and old-age dependency ratio). The results indicate the occurrence of absolute (unconditional) beta-convergence of the variables that characterise labour resources. No unambiguous confirmation of sigma-convergence, i.e. a significant reduction in the diversification of the provinces in terms of the studied variables, was obtained. Similarly, the occurrence of gamma-convergence, i.e. a significant change in the positions of the provinces in terms of labour resources, was not unambiguously confirmed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 75-100
Keywords: social convergence; regional convergence; labour resources; konwergencja społeczna; konwergencja regionalna; zasoby pracy